MAKNA KEBENARAN ALLAH DALAM KITAB ROMA - Theodorus Miraji; Hery Susanto (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2022)
Abstract: God's righteousness is God authority that given to human as a gift. Human could not find it by himself within or in the world because they have fallen into sin. God righteousness is universal and independent, means not depending on human condition, but fully on God sovereign.Jesus Christ has become the center of God revelation. In which all who believe in Him will put to right and will be saved. The consequence from trusting Jesus will make repentance, that cause someone leave their past life and become new creation (in quality). It because that the righteousness has forensic character and pass through whole life of a person. Righteousness will be brighter if a person who has received Jesus, willing to spread the Gospel to new people. Believers are not living with fear to the Law as in Old Testament, but live in grace that full of joy that will eliminate fear. Paul's Theology about God righteousness put human into the same position before God, no one is more special than others, all sins before God. Even though in Old Testament there was privilege to Abraham descendants, but it won’t make Jews the most special one. Jesus sacrifice has destruct boundaries and reconstruct new living. The past (privilege) will have no effect Keywords: Righteousness, Rome, Paul